Draft Annual Plan 1986-87 Volume : V General Areas Government of Assam - Planning Commission (Planning Commission, 1986)
The Planning Commission has allocated a sum of Rs.15.23 crores during the year 1985-86 against our proposal of Rs. 21.88 crores in the Draft Plan. It may be stated here that the Annual Plan allocation for the year 1984-85 was Rs. 14.95 crores. This includes committed liabilities of Rs. 12.00 crores. As per Guideline given in the approach paper the above committed liabilities of staff and other on going schemes of Sixth Five year Plan were not included in the Draft Annual Plan 1985-86 on the presumptions that all such liabilities would be transferred to Non-Plan side.
Government of Assam, Planning and Development Department